(untitled) (Research, Society and Development, 2020)
The theoretical essay ‘The relevance of Socialist Pedagogy: a theoretical essay’ aims to present reflections on the relevance of Soviet Socialist Pedagogy from the perspective of Bemvindo, Filonov, Felix & Gasparin, Hobsbawn, Machado, Marx and Engels, Shulgin, Trotsky among others. Methodologically, this research is classified as bibliographic, descriptive and qualitative. Business history issues are addressed with the intention of analyzing the designs after the Russian Revolution of 1917, under an eyepiece of education and work relationship and the thinking of the main authors of Soviet Socialist Pedagogy.